Gasoline partially premixed combustion: high effi ciency, low NOx and low soot by using an advanced combustion strategy and a compression ignition engine. (1st January 2012) - Manente, Vittorio; Johansson, Bengt; Tunestal, Per; Sonder, Marc; Serra, Simone
A light-duty engine Volvo D5 was run with gasoline to demonstrate that high-octane number fuels, in compression ignition engines, are able to achieve high effi ciency, low NOx and soot simultaneously. An advanced three stage injection strategy was developed. A load sweep was performed between 6 and 17 bar IMEP and 2000 rpm. Gross indicated effi ciency stays fairly constant at 47% with very low NOx and soot. In the second section of the paper, diesel was compared with gasoline, while in the fi nal part the commercial 140°UA nozzle was compared with the narrower one, 120°, used in the above-mentioned experiments.